Probiotics Intake as Adjunct Therapy for Infected Health-Care with SARS COV-2 - Anna Surgean Veterini; Eighty Mardiyan Kurniawati; Hamzah; Subijanto Marto Soedarmo; Cita Rosita Sigit Prakoeswa; Damayanti Tinduh (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objectives: We performed this case-control observational study to evaluate the comparison of the length ofduration of SARS COV-2 infection and the cycle threshold (Ct) value of reverse-transcriptase polymerasechain reaction (RT-PCR) nasopharynx swab between the probiotics intake (case) group and the nonprobiotics intake (control) group.Materials and Methods: Our study was a case-control study involving 15 cases and 15 controls matchfor RT-PCR positive results. The participants were healthcare consisted of registrars, consultants, andnurses. Each participant was interviewed by google forms using a structured questionnaire to collect sociodemographic characteristics, diet, therapy from a pulmonologist, and adjunct therapy.Results: The total participants consisted of 15 males and 15 females. 4 participants in the case group hadfebrile, 1 participant with anosmia, 1 participant with febrile, nausea, and vomit before they consumedprobiotics, and 9 participants without clinical complaints. One participant in the control group had feveredand cough, 14 participants without clinical complaints—1 participant with co-morbidities in the controlgroup. The data of age, duration of infection, and cycle threshold (Ct) value were in the normal distribution.Analysis results using SPSS 21.00 show no significant differences in the course of disease between the casegroup and the control group. We found 2 participants in the control group had re-infection, while there wasno re-infection in the case group.Conclusion: The present study’s finding may imply future care for the viral infection through theimmunomodulation mechanism by probiotics consumption.